Google Trends Potential for Detecting a Large-scale Mental Health Issue: A Study during Pandemic in Indonesia - Urfa Khairatun Hisan; Muhammad Miftahul Amri; Dwi Sulisworo; Indah Rahmawati; Tarisa Afira Pramesti (Universitas Aisyah Pringsewu, 2023)
Background: Attempts have been made to overcome COVID-19. However, one problem remains present: mass-mental health issues. Numerous studies have shown increased mental problems during the pandemic. The feasibility of using search engine trends and online sentiment analysis as an additional surveillance tool to detect large populations’ problems has been explored. Objective: We examined Google Trends' potential to detect early symptoms of mass-mental issues. Methods: This study is conducted on the Indonesian population. We investigate Bahasa Indonesia words related to signs of mental disorders: ‘merasa sendiri’, ‘khawatir’, ‘mudah marah’, ‘pemarah’, ‘cemas’, and ‘takut’. Each keyword means 'loneliness', 'afraid', 'easy to get angry', 'short-tempered', 'anxious', and 'fear'. The search range is set between February 2020-2022. The assumptions are that people tend to self-diagnose by online searching with keywords that match their condition, find solutions on the internet due to the limited offline interactions during the pandemic, and find information online before going to professionals. Results: It is observed that the search frequency on Google search engine follows the COVID-19 infection trends in Indonesia. It does suggest that with the increase in the COVID-19 infection rate, the search frequency of keywords associated with signs of mental issues also increased. Following the improved pandemic conditions, the search frequency of those keywords is also reduced. Conclusion: This work has demonstrated Google Trends’ potential as an adjuvant surveillance tool to detect mass-mental health issues. It should be noted that these tools should be used only to provide insight into the populations’ conditions rather than as the main indicators. Abstrak: Latar Belakang: Berbagai upaya telah dilakukan untuk mengatasi COVID-19. Namun, terdapat satu masalah yang tetap bertahan: isu kesehatan mental massal. Sejumlah penelitian menunjukkan peningkatan masalah mental selama pandemi. Akhir-akhir ini, kelayakan menggunakan tren mesin pencari dan analisis sentimen daring sebagai alat surveilans tambahan untuk mendeteksi masalah populasi massal semakin sering dieksplorasi. Tujuan Penelitian: Kami menginvestigasi potensi Google Trends untuk mendeteksi gejala awal masalah mental massal. Metode: Studi ini dilakukan pada populasi Indonesia. Kami menginvestigasi kata-kata Bahasa Indonesia yang berhubungan dengan tanda-tanda gangguan kesehatan jiwa: 'merasa sendiri', 'khawatir', 'mudah marah', 'pemarah', 'cemas', dan 'takut'. Setiap kata kunci berarti 'loneliness', 'afraid', 'easy to get angry', 'short-tempered', 'anxious', dan 'fear' dalam Bahasa Inggris. Rentang pencarian ditetapkan antara Februari 2020-2022. Asumsinya, masyarakat cenderung melakukan self-diagnosis dengan melakukan pencarian daring dengan kata kunci yang sesuai dengan kondisinya, mencari solusi di internet karena terbatasnya interaksi luring selama pandemi, dan mencari informasi secara daring sebelum ke profesional. Hasil: Teramati bahwa frekuensi pencarian di mesin pencari Google mengikuti tren infeksi COVID-19 di Indonesia. Hal ini menunjukkan bahwa seiring dengan peningkatan tingkat infeksi COVID-19, frekuensi pencarian kata kunci yang terkait dengan tanda-tanda masalah mental juga meningkat. Mengikuti kondisi pandemi yang membaik, frekuensi pencarian kata kunci tersebut juga berkurang. Kesimpulan: Penelitian ini telah mendemonstrasikan potensi Google Trends sebagai alat surveilans tambahan untuk mendeteksi masalah kesehatan mental massal. Perlu diingat bahwa alat seperti Google Trends harus digunakan hanya untuk memberikan gambaran indikasi tentang kondisi suatu populasi alih-alih sebagai indikator utama.